2021
DOI: 10.3390/su13084199
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Factors in University Students’ Self-Evaluation for Sustainability

Abstract: Background: Self-evaluation is a multidimensional construct that has raised increasing interest within educational research at different educational stages. Different studies have pointed out the important role that Student Self-Assessment plays in improving student learning and ensuring the sustainability in instructional and evaluation processes. Method: The aim of this study with 630 university students is to analyze how engagement profiles and study strategies (measured by questionnaire) can predict the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…In this study, it was shown that engagement profiles and study strategies are important predictors of SSA. This finding is consistent with other research where engagement have been related, such as the studies of [51] and [118].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, it was shown that engagement profiles and study strategies are important predictors of SSA. This finding is consistent with other research where engagement have been related, such as the studies of [51] and [118].…”
Section: Discussionsupporting
confidence: 92%
“…In general, as different researchers have repeatedly reported, student satisfaction is a very reliable indicator for measuring the success of the implementation of E-learning-based initiatives (strong relationship between students' perception of their academic performance and their degree of satisfaction in E-learning environments) [37,[47][48][49][50]. Subsequently, Student Learning Achievements (SSA) has been widely used as an evaluation mechanism in the educational field [51][52][53][54]. The SSA is a powerful tool to evaluate the performance of E-learning strategies in higher education, but even more important is this evaluation in primary and secondary school, given that the students' preparation is slower, since they are in an earlier period of their training.…”
Section: Development Of the Conceptual Model (Research Model And Hypo...mentioning
confidence: 99%
“…In a study with 11th grade students [27], it was found that 90% self-assessed themselves at levels higher than the evaluator, suggesting that students are not familiar with self-assessment and because they trust the teacher as the only one evaluator of its performance. Another study with university students reveals that students with higher performance and more involvement tend to show greater skills with self-assessment; and students with better study habits tend to have better scores, greater confidence, and better self-assessment skills [28]. A study with peer assessment and self-assessment of group work in a computer programming unit reveals that the more students know, the more they think they do not know, and the less they know, the more ignorance they have about their knowledge [29].…”
Section: Self-assessmentmentioning
confidence: 99%
“…Experts do not only focus on the importance of self-assessment in the academic environment, but also in the following contexts: employment (e.g. Zimmerman, Moylan, Hudesman, White and Flugman, 2011;McNall and Michel, 2017;León, Augusto-Landa and García-Martínez, 2021;Tomšíková, Smékalová and Slavík, 2014;Novotná and Nišponská, 2017;Fišer et al, 2016), the influence of self-assessment in the overall educational career of an individual (e.g. Karaman, 2021), when selfassessment supports and maintains students' approach during the beginning of schooling and throughout the whole primary school (Vasileiadou, Karadimitriou, 2021;Panadero, Jonsson, Botella, 2017;Broadfoot, 1996;Laufková, 2017).…”
Section: Introductionmentioning
confidence: 99%